Application of the Demonstration Learning Method in Improving Student Learning Achievement in the Eyes Islamic Religious Education Lessons - Miftahul Romdon (Penerbit Hellow Pustaka, 2023)
This paper was written to find out the increase in student achievement in applying the demonstration learning method to PAI subjects in class XI at Indramayu National Vocational School and to find out the constraints and effectiveness of applying the demonstration learning method to PAI class XI subjects at Indramayu National Vocational School. The method used in this study is a qualitative method using a type of field research with data collection techniques through observation, interviews, and documentation. The sample in this study were students of class XI at SMK Nasional Indramayu. The conclusion of this study is that the application of demonstration learning methods has a positive effect on improving student achievement as indicated by an increase in the value of student learning outcomes in the subject matter being demonstrated. There are several supporting factors in the application of this demonstration learning method that make this learning method effective in increasing learning achievement, namely the factor of the teaching staff, and the factor of the condition of the school. As for the obstacles, namely coming from within the students themselves, namely the interests and attention of students as well as school facilities and infrastructure that support the learning process.